Vaccines Are Not Evenly Distributed? Threats To Human Rights And Herd Immunity - Yohanes Firmansyah; Imam Haryanto (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2021)
The Covid-19 pandemic has had a significant impact on all humankind by causing losses in all aspects of life. Like other infectious diseases, vaccines are the most potent weapon that human has in fighting the COVID-19 pandemic. But problems arise over who has the right to get the COVID-19 vaccine. All social issues began to emerge and caused clashes between human rights and the inadequate effectiveness of vaccines if they were not given to the whole community (Herd immunity was not achieved). This research is a literature review research with data searches conducted on various search engines such as Google Scholar. This research is qualitative research, where all materials and literature that have been collected during the research period will be reviewed with three types of approaches, namely juridical, conceptual and analytical approaches. The results of the study describe that the ideal goal of the Vaccination action is to eradicate COVID-19 cases. One of the efforts to achieve this goal is to establish a Herd-immunity and ensure that every citizen has his right to vaccinate fairly. Indonesia launched a free COVID-19 vaccination program as of December 16, 2020, as a form of the State’s implementation in upholding Human Rights, the 1945 Constitution, Law No. 39 of 1999, and formed herd-immunity in the context of handling COVID-19 as effectively and optimally as possible